Structure of the posthepatic septum and its influence on visceral topology in the tegu lizard, Tupinambis merianae (Teiidae : Reptilia) - Klein, W.; Abe, Augusto Shinya [UNESP]; Andrade, D. V.; Perry, S. F. (Wiley-Blackwell, 2003)
The posthepatic septum (PHS) divides the body cavity of Tupinambis merianae into two parts: the cranial one containing the lungs and liver and the caudal one containing the remaining viscera. The PHS is composed of layers of collagenous fibers and bundles of smooth muscle, neither of which show systematic orientation, as well as isolated blood vessels, lymphatic vessels, and nerves. Striated muscle of the abdominal wall does not invade the PHS. The contractions of the smooth muscles may stabilize the pleurohepatic cavity under conditions of elevated aerobic needs rather than supporting breathing on a breath-by-breath basis. Surgical removal of the PHS changes the anatomical arrangement of the viscera significantly, with stomach and intestine invading the former pleurohepatic cavity and reducing the space for the lungs, Thus, the PHS is essential to maintain the visceral topography in Tupitionibis. J. Morphol. 258:151-157, 2003. (C) 2003 Wiley-Liss. Inc.
Keywords: Tupinambis; lizard; posthepatic septum; functional morphology; histology; X-ray; electron microscopy